Relevansi Pendekatan Deep Learning dengan Semangat Kurikulum Merdeka pada Mata Pelajaran Fikih - Aini Nur Ma’rifah; Umi Salamah; Binti Muthmainah (MGMP PAI SMP BINTAN, 2026)
This study aims to analyze the relevance of the deep learning approach to the spirit of the Merdeka Curriculum in Fiqh learning for eighth-grade students at MTs Al Mubarok Uman Agung, Central Lampung. In this study, the deep learning approach is grounded in three main elements: meaningful learning, mindful learning, and joyful learning. This research employed a qualitative approach with a descriptive design. The research subjects consisted of a Fiqh teacher and eighth-grade students. Data were collected through classroom observations, in-depth interviews, and documentation, while data analysis was conducted using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that meaningful learning was implemented by connecting Fiqh materials with students’ real-life experiences, making learning more contextual and meaningful. Mindful learning was reflected in students’ reflective thinking, learning awareness, and deep understanding of the values and purposes of Islamic law. Meanwhile, joyful learning was evident in a supportive and enjoyable learning atmosphere that fostered positive emotional engagement. These three elements demonstrate strong alignment with the principles of the Merdeka Curriculum, which emphasizes student-centered learning and character development. The study concludes that the deep learning approach is relevant and effective in supporting the implementation of the Merdeka Curriculum in Fiqh learning within a pesantren-based madrasah context.